PEMBUATAN PROTOTYPE PEMBANGKIT LISTRIK HYBRID TENAGA MATAHARI DAN TENAGA ANGIN LAPORAN TUGAS AKHIR VAWT (VERTICAL AXIS WIND TURBINE) DUA TINGKAT - , GUSMAN ARIF ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of fossil fuels for conventional power plants in the long term will drain oil, gas and coal resources. So renewable energy utilization that more environmentally friendly concepts such as wind and solar heat must be optimized. This is the our reason to make hybrid consep betwen wind and solar heat. The concept of hybrid power generation system is a combination of solar cell and wind turbine. Combination of both power plants were intended to maximize power plant performance to support each other, and during the day when there is sufficient light intensity, the solar cell will work and if the solar cell can not work like at night or insufficient light intensity and then there is wind power available the wind turbine will work as a power plant and in reverse case. And if two of the power plant working simultaneously the electrical energy generated will be even greater.